Failure and sensitivity analysis of a reconfigurable vibrating screen using finite element analysis. (October 2017) - Ramatsetse, Boitumelo; Mpofu, Khumbulani; Makinde, Olasumbo
Highlights: We used industrial case study to carry out a failure study on the different vibrating screen sub-systems in order to lessen frequent failure. We perform a sensitivity analysis on the RVS machine using different loading to determine the stress regions using ANSYS ® . We examine the stress distributions on the RVS machine and then implement improvements using lessens from industry as well as experts judgements. Abstract: In mineral processing industries vibrating screens operate under high structural loading and continuous vibrations. In this regard, this may result in high strain rates, which may often lead to structural failure or damage to the screen. In order to lessen the possibility of failure occurring, theories and techniques for analyzing machine structures are investigated and applied to perform a sensitivity study of a newly developed vibrating screen. Structural strength and stability of a vibrating screen is essential to insure that failure doesn't occur during production. In this paper a finite element analysis (FEA) on a reconfigurable vibrating screen (RVS) is carried out to determine whether the structure will perform as desired under extreme working conditions at the different configurations of 305 mm × 610 mm, 305 mm × 1220 mm and 610 mm × 1220 mm. This process is aimed at eliminating unplanned shutdowns and minimizes maintenance cost of the equipment. Each component of a screen structure is analyzed separately, stress and displacement parameters are determined based on dynamic analysis. In addition, a modal analysis was carried out for the first three (3) modes at frequency f of 18.756 Hz, 32.676 Hz and 39.619 Hz respectively. The results from the analysis showed weak points on the side plates of screen structure. Further improvements were incorporated to effectively optimize the RVS structure after undergoing an industrial investigation of similar machines.